2012
DOI: 10.1261/rna.035287.112
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Trm7 interacts with distinct proteins for critical modifications of the tRNAPhe anticodon loop

Abstract: Post-transcriptional modification of the tRNA anticodon loop is critical for translation. Yeast Trm7 is required for 29-O-methylation of C 32 and N 34 of tRNA Phe , tRNA Trp , and tRNA Leu(UAA) to form Cm 32 and Nm 34 , and trm7-D mutants have severe growth and translation defects, but the reasons for these defects are not known. We show here that overproduction of tRNA Phe suppresses the growth defect of trm7-D mutants, suggesting that the crucial biological role of Trm7 is the modification of tRNA Phe . We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
182
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(188 citation statements)
references
References 76 publications
5
182
1
Order By: Relevance
“…The suppression of the pus3Δ temperature sensitivity by increased dosage of tRNA Gln(UUG) emphasizes that, as with other modifications mutants, there is a primary target tRNA for which the modification appears to have the major biological effect (Esberg et al 2006;Björk et al 2007;Phizicky and Alfonzo 2010;Dewe et al 2012;Guy et al 2012). Two previous reports also emphasize a central role of mcm 5 s 2 U of tRNA Gln(UUG) : the high copy suppression by tRNA Gln (UUG) and tRNA Lys(UUU) of the multiple phenotypes of elp mutants, which lack the cm 5 U moiety (Esberg et al 2006); and the enhanced high copy suppression by tRNA Gln(UUG) (in addition to tRNA Lys(UUU) ) of the lethality of elp3Δ tuc1Δ mutants, which lack both the cm 5 U and s 2 U moieties of mcm 5 s 2 U (Björk et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppression of the pus3Δ temperature sensitivity by increased dosage of tRNA Gln(UUG) emphasizes that, as with other modifications mutants, there is a primary target tRNA for which the modification appears to have the major biological effect (Esberg et al 2006;Björk et al 2007;Phizicky and Alfonzo 2010;Dewe et al 2012;Guy et al 2012). Two previous reports also emphasize a central role of mcm 5 s 2 U of tRNA Gln(UUG) : the high copy suppression by tRNA Gln (UUG) and tRNA Lys(UUU) of the multiple phenotypes of elp mutants, which lack the cm 5 U moiety (Esberg et al 2006); and the enhanced high copy suppression by tRNA Gln(UUG) (in addition to tRNA Lys(UUU) ) of the lethality of elp3Δ tuc1Δ mutants, which lack both the cm 5 U and s 2 U moieties of mcm 5 s 2 U (Björk et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…At residue 37, mutants lacking t 6 A 37 (N 6 -threonlycarbamoyladenosine) (El Yacoubi et al 2011;Srinivasan et al 2011) or m 1 G 37 grow very poorly , and lack of i 6 A 37 (N 6 -isopentenyladenosine) results in reduced nonsense suppression (Dihanich et al 1987) and tRNA gene-mediated silencing (Pratt-Hyatt et al 2013), as well as increased resistance to certain antifungal drugs (Suzuki et al 2012). Similarly, lack of Cm 32 and Nm 34 due to lack of TRM7 leads to poor growth because of reduced function of tRNA Phe (Pintard et al 2002;Guy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Trm7 Trm732 heterodimer is responsible for 29O methylation of C 32 (Cm 32 ), whereas the Trm7 Trm734 heterodimer is responsible for 29O methylation at position 34 (Cm 34 /Gm 34 and ncm 5 Um 34 ), indicating that Trm734 and Trm732 direct correct nucleoside modification sites (Guy et al 2012). Moreover, Trm112 is the activating subunit for both Trm9 and Trm11, required for mcm 5 U 34 / mcm 5 s 2 U 34 and m 2 G 10 , respectively, as well as for Mtq2, required for methylation of protein termination factor Sup45 and Bud23, required for rRNA G1575 methylation (Phizicky and Hopper 2010;Liger et al 2011;Figaro et al 2012).…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%
“…A final question regarding specificity is whether a given modification requires a prior different modification(s). Until recently there were no known examples of this type of specificity; however, it has now been shown that completion of yW modification at position 37 of tRNA Phe requires prior modification of Gm 34 by Trm7 (Guy et al 2012).…”
Section: Removal Of 59 Leader and 39 Trailer Sequences From Pre-trnasmentioning
confidence: 99%
“…These include TrmJ and TrmL, which catalyze the methylation of the ribose of nucleosides on, respectively, positions 32 and 34 (Purta et al 2006;Benitez-Paez et al 2010). Surprisingly, in Eukarya, methylation of the ribose moiety of nucleosides 32 and 34 is carried out by the completely unrelated Trm7 enzyme, assisted by either the auxiliary protein Trm732 or Trm734 (Pintard et al 2002;Guy et al 2012).…”
Section: Introductionmentioning
confidence: 99%